1991
DOI: 10.1037/0022-3514.61.6.857
|View full text |Cite
|
Sign up to set email alerts
|

Prototypes in the courtroom: Lay representations of legal concepts.

Abstract: To select a verdict, jurors must integrate the evidence presented at trial with the law presented in the judge's instructions. Jurors are assumed to have no prior knowledge of the law or to set aside that knowledge after instruction. Several experiments (N = 489) tested these assumptions and revealed that (a) uninstructed Ss had built naive representations of crime categories that included legally incorrect information; (b) these representations contained category prototypes that influenced Ss' verdict choices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
250
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(269 citation statements)
references
References 43 publications
16
250
0
3
Order By: Relevance
“…The idea that jurors-rather than being blank slates-have idiosyncratic knowledge, stereotypes, and prototypes to guide their decision-making for legal tasks has a substantial theoretical and empirical foundation (see, e.g., Finkel, 1995;Smith, 1991Smith, , 1993Smith & Studebaker, 1996;Stalans, 1993;Stalans & Diamond, 1990). For example, in an investigation of jurors' prototypes of insanity, Skeem and Golding (2001) demonstrated that jurors' interpretations of case information as well as the verdicts they rendered were influenced by the prototype of insanity to which they subscribed.…”
Section: Negative Attitudes About Sexual Offendersmentioning
confidence: 99%
“…The idea that jurors-rather than being blank slates-have idiosyncratic knowledge, stereotypes, and prototypes to guide their decision-making for legal tasks has a substantial theoretical and empirical foundation (see, e.g., Finkel, 1995;Smith, 1991Smith, , 1993Smith & Studebaker, 1996;Stalans, 1993;Stalans & Diamond, 1990). For example, in an investigation of jurors' prototypes of insanity, Skeem and Golding (2001) demonstrated that jurors' interpretations of case information as well as the verdicts they rendered were influenced by the prototype of insanity to which they subscribed.…”
Section: Negative Attitudes About Sexual Offendersmentioning
confidence: 99%
“…Rather, it provides a sound, general depiction of the process of juror decision making and story construction. This and other studies (Kuhn et al, 1994;Smith, 1991Smith, , 1993Weinstock & Cronin, 2003), however, suggest that accounts of juror decision making must consider differences not only in representations people hold, but in the cognitive ability and understanding of the means of constructing and justifying knowledge claims that mediate the representational process. As the thinking underlying juror argument skill may be amenable to improvement (Baron, 1985(Baron, , 1993Kuhn, 1999aKuhn, , 2001Stanovich, 1999), understanding jurors' reasoning should lead to optimizing it.…”
Section: Resultsmentioning
confidence: 85%
“…These earlier studies typically found that people who had been induced to feel traditionally negatively valenced emotions would be predisposed towards a more systematic style of processing, while those people who were induced to feel positively valenced emotions favored the use of more heuristic styles of processing (Bless, Bohner, Schwarz & Strack, 1990;Mackie & Worth, 1989;1991).…”
Section: Emotion Induction Techniquesmentioning
confidence: 99%
“…These valence-oriented studies proposed different mechanisms of action for their findings including capacity arguments (that a state of cognitive overload results from the fact that positive emotions are intricately intertwined with other conceptual notes; Mackie & Worth, 1989;1991) and motivational bases (in order to maintain or achieve positive states by avoiding or remedying negative states, we must utilize systematic thought processes; Bless et al, 1990;Wegener & Petty, 1994;Wegener, Petty, & S. M. Smith, 1995). Bless et al (1996) modified the notion that happiness lessens the motivation to deeply process information.…”
Section: Emotion Induction Techniquesmentioning
confidence: 99%
See 1 more Smart Citation